ADVERTISEMENT IN THE BANKING SECTOR: ANALYSIS AND COMPARISON BETWEEN PRIVATE AND PUBLIC LIMITED BANKS - Anita Ramrakhyani, N .K. Srivastava, Surya Prakash (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
As the whole world is in competition so is the banking industry. To beat the competition in quantity and price and to win the prospects there is a need to advertise the products and services to the right audience at the right time. The scope of the paper is to examine the relationship between advertising by public and private sector banks and its possible influence on potential customers to select their bank. The survey collected 300 questionnaire to provide the Imperial database for enquiry and reached to the conclusion of existence and implication of advertisement in banking sector. The paper concludes that in comparison to exhibition, trade shows, cinema, sports events ,weekly and monthly magazines, hoardings, etc are very less influential as compared to TV advertisements, newspapers, poster display, pamphlets, mobile and Internet media in the present scenario. The paper compares and evaluates the advertising campaigns and strategies adopted by public and private limited banks and winds up with the findings that the primary objective of advertising is to create knowledge of the organization and the products and services it offers. It also facilitates to set up a link between consumers and the organization, in order to attain some sort of emotional bond.